Development And Evaluation Of Miconazole Nitrate Loaded Niosomal Suspension - Singh, Navneet; Singh, Amerendra; Mishra, Jai Narayan (Journal of Neonatal Surgery, 2025)
Niosomes, which are vesicular drug delivery vehicles made mostly of non-ionic surfactants, have a number of benefits over traditional formulations. Niosomes are a safer option than other nanoparticle-based carriers because of their improved stability, biodegradability, and decreased toxicity. These vesicles are very adaptable because they can contain both hydrophilic and lipophilic medications. They are especially useful in systemic applications like cancer therapy as well as topical and transdermal formulations like gels and creams because of their capacity to enhance drug penetration, maintain release, and target particular sites. The goal of this research is to maximize stability and integrity by optimizing the formulation of niosomes in the lab and testing various surfactant and cholesterol ratios. The study also attempts to evaluate the niosomal system's release behavior and drug loading efficiency. Thorough characterization methods, such as FTIR, TEM, SEM, and zeta potential analysis, are used to assess the physicochemical stability, morphology, and general performance of the prepared formulations